Tradycja śpiewów przed kazaniem i po kazaniu w zbiorach pieśni kościelnych na Górnym Śląsku w XIX i XX wieku - Reginek, Antoni (Studia Pastoralne, 2026)
The songs related to the proclamation of the word of God belong to the oldest ones in the Polish language and form a group of so-called „sermon songs”. They were helpful in the active participation in the liturgy of the Eucharist when it was celebrated in Latin. Especially in the XIX and XX centuries, the tradition of their performance, in and out of the liturgy, was very alive also in Silesia. The old Polish sources of Church songs show an extensive collection of songs intended to be sung before and after a sermon. In the actual repertory of Church songs there are more than a dozen of them. Regarding the theological content of these songs sung before the sermon are the beseeching prayers for the light of the Holy Spirit and God’s wisdom for the preacher and listeners. When they are sung after the sermon, they are a begging for God’s help for the fulfillment of the teaching. Nowadays, the importance of these songs is decreasing and this process is related to the Second Vatican Council’s liturgical reform which underlines the function of the homily and the continuity of the Liturgy of the Word. However, in these circumstances it seems to be still possible to maintain the tradition of singing and imploring the grace of the Holy Spirit.